1993
DOI: 10.1038/361549a0
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of apical membrane water channel of rat kidney collecting tubule

Abstract: Concentrating urine is mandatory for most mammals to prevent water loss from the body. Concentrated urine is produced in response to vasopressin by the transepithelial recovery of water from the lumen of the kidney collecting tubule through highly water-permeable membranes. In this nephron segment, vasopressin regulates water permeability by endo- and exocytosis of water channels from or to the apical membrane. CHIP28 is a water channel in red blood cells and the kidney proximal tubule, but it is not expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
538
1
10

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 940 publications
(566 citation statements)
references
References 19 publications
15
538
1
10
Order By: Relevance
“…In fact, AQP1 knockout mice were found to develop polyuria due to both a defective water reabsorption mechanism in the proximal tubules and a dysfunctional countercurrent mechanism in the inner medulla (26). Other renal AQPs, such as AQP2, AQP3, and AQP4, are all present in the collecting ducts and are directly involved in water reabsorption to produce the final concentrated urine (2,13,14). Very recently, Maeda et al (16) generated AQP7 knockout mice and reported on the phenotype characteristics only in the adipocytes, where AQP7 constitutes a glycerol-releasing pathway without which hypoglycemia occurs after starvation.…”
mentioning
confidence: 99%
“…In fact, AQP1 knockout mice were found to develop polyuria due to both a defective water reabsorption mechanism in the proximal tubules and a dysfunctional countercurrent mechanism in the inner medulla (26). Other renal AQPs, such as AQP2, AQP3, and AQP4, are all present in the collecting ducts and are directly involved in water reabsorption to produce the final concentrated urine (2,13,14). Very recently, Maeda et al (16) generated AQP7 knockout mice and reported on the phenotype characteristics only in the adipocytes, where AQP7 constitutes a glycerol-releasing pathway without which hypoglycemia occurs after starvation.…”
mentioning
confidence: 99%
“…The hereditary (congenital) form of NDI is relatively rare, and is known to be caused by mutations in two genes, the arginine vasopressin type 2 receptor (AVPR2) and the water channel aquaporin 2 (AQP2) [1][2][3][4]. These two genes encode two membrane proteins that are oppositely located at the basolateral and apical membranes of the collecting duct principal cells, respectively, and constitute the fundamental components of urine concentrating machinery [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…15,16 When living cells were incubated with fluorescently labeled transferrin to label endosomes ( Figure 4B) and were subsequently subjected to confocal immunofluorescence microscopy to detect AQP2 and late endosomes/lysosomes with an antibody against LAMP 1 ( Figure 4D), this triple labeling protocol provided evidence for co-distribution of wt AQP2 with a limited number (Ïł20 to 30%) of transferrin-loaded endosomes ( Figure 4C). However, the limited x-y resolution of confocal immunofluorescence (Յ200 nm) allows no statement that wt AQP2 actually co-localizes with endosomes.…”
Section: Intracellular Distribution Of Wild-type and Mutant Aqp2mentioning
confidence: 99%
“…12 AQP2 belongs to the large family of AQPs, 13,14 and is a 29-kd polytope membrane protein that contains a single N-glycosylation site and two phosphorylation sites, and is present in the principal cells of renal collecting ducts. 15,16 In states of hypernatremia or hypovolemia, translocation of phosphorylated AQP2 homotetramers from vesicles to the apical plasma membrane of the principal cells is triggered by a signal transduction cascade induced by arginine-vasopressin. 16 -18 Alike to normal human kidney, 19 wild-type (wt) AQP2, when expressed in Xenopus oocytes 20,21 or various mammalian cell lines, 18,22 existed as a nonglycosylated 29-kd form.…”
Section: Mutations In the Water Channel Aquaporin-2 (Aqp2) Can Cause mentioning
confidence: 99%